Barriers and facilitators to the provision of optimal obstetric and neonatal emergency care and to the implementation of simulation-enhanced mentorship in primary care facilities in Bihar, India: a qualitative study - Melissa C. Morgan; Jessica Dyer; Aranzazu Abril; Amelia Christmas; Tanmay Mahapatra; Aritra Das; Dilys M. Walker (BMC, 2018)
Abstract Background Globally, an estimated 275,000 maternal deaths, 2.7 million neonatal deaths, and 2.6 million third trimester stillbirths occurred in 2015. Major improvements could be achieved by providing effective care in low- and middle-income countries, where the majority of these deaths occur. Mentoring programs have become a popular modality to improve knowledge and skills among providers in low-resource settings. Thus, a detailed understanding of interrelated factors affecting care provision and mentorship is necessary both to improve the quality of care and to maximize the impact of mentoring programs. Methods In partnership with the Government of Bihar, CARE India and PRONTO International implemented simulation-enhanced mentoring in 320 primary health clinics (PHC) across the state of Bihar, India from 2015 to 2017, within the context of the AMANAT mobile nurse mentoring program. Between June and August 2016, we conducted semi-structured interviews with 20 AMANAT nurse mentors to explore barriers and facilitators to optimal care provision and to implementation of simulation-enhanced mentorship in PHCs in Bihar. Data were analyzed using the thematic content approach. Results Mentors identified numerous factors affecting care provision and mentorship, many of which were interdependent. Such barriers included human resource shortages, nurse-nurse hierarchy, distance between labor and training rooms, cultural norms, and low skill level and resistance to change among mentees. In contrast, physical resource shortages, doctor-nurse hierarchy, corruption, and violence against providers posed barriers to care provision alone. Facilitators included improved skills and confidence among providers, inclusion of doctors in training, increased training frequency, establishment of strong mentor-mentee relationships, administrative support, and nursing supervision and feedback. Conclusions This study has identified many interrelated factors affecting care provision and mentorship in Bihar. The mentoring program was not designed to address several barriers, including resource shortages, facility infrastructure, corruption, and cultural norms. These require government support, community awareness, and other systemic changes. Programs may be adapted to address some barriers beyond knowledge and skill deficiencies, notably hierarchy, violence against providers, and certain cultural taboos. An in-depth understanding of barriers and facilitators is essential to enable the design of targeted interventions to improve maternal and neonatal survival in Bihar and related contexts.